Philosophical, religious and supernatural elements in emily dickinson's poetry: a rereading - Veeramankai, S.Y. (University of Jaffna, 2016)
Emily Dickinson was born on December 10, 1830 in a small American town called Amherst. She has rightly been described as “A Poet Restored”. The most surprising thing about Dickinson is that she has deliberately adopted a life of privacy and seclusion. Emily Dickinson's unique contributions to American literature are her poetic treatment of the themes of death, immortality and God. Some of her poems on death deal with the sensations of the dying person or the physical experiences as the soul leave the body. The main objective of this research is to analyse philosophical, religious and supernatural elements in Emily Dickinson's Poetry. A large number of her poems explore the nature of pain, its stages and its effects upon the human soul and finally its relation with death, immortality and God. Emily's poems deal with misery, anguish and despair are closely related to her philosophy of life. The range of her poetry deals with the treatment of death varies from a philosophical examination of death's relation with love to a grim consideration of its physical processes. This paper analyses how pain elevated man new heights establishing an aristocratic bond with others who experience similar anguish. The poems express philosophical, religious and supernatural ideas in life. Analytical, descriptive and comparative methods will be used in this research paper. Data is collected from texts, books, Journals, magazines and articles. This research paper will be helpful to expand students' skills and ability in research field and enlighten their knowledge in Emily Dickinson's poetry and English literature
Keywords: Death; God; Immortality; Pain; Philosophy; Soul